BABILANGAN: THE TRADITION OF BANJARESE PEOPLE BEFORE MARRIAGE IN FIQH MUWAZANAH PERSPECTIVE - Wafi, Akhmad; Muzainah, Gusti; Siti Maghfirah; Nur Hikmah (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
The custom of "Babilangan" is a tradition of the Banjar people who calculate the value of Arabic letters in the name of the bride-to-be to predict the compatibility and harmony of the household. This tradition reflects prudence in choosing a partner with the aim of avoiding potential disharmony in the marriage. However, the results of Banjar's prophecy often influenced the decision to get married, even to the point of canceling the wedding plan if it was considered unsuitable. From the perspective of muwazanah jurisprudence, this custom raises a controversy between the real benefits of marriage, such as maintaining offspring and carrying out the Sunnah of the Prophet, and the bad impact that is possibility of divorce. This study, which uses a normative legal method with a fiqh approach to the rules, assesses that the real benefits of marriage are more important than the alleged bad impact of predicted. The rules of fiqh state, "Definite benefits should not be abandoned because of the alleged mafsadah." Therefore, while Babilangan is useful as a measure of estimation, the decision to get married should not depend entirely on the outcome of the prophecy. Brides-to-be are advised to consider mental, financial, and religious readiness in choosing a partner, because these aspects are more relevant in realizing a harmonious household according to Islamic law. With this approach, the Babilangan tradition can be preserved as part of local wisdom without putting aside religious principles.